"Sajarah Cina"; A nineteenth-century apology in Javanese - van der Molen, Willem (Wacana, Journal of the Humanities of Indonesia, 2017)
The sometimes precarious position of the Chinese in Indonesia has a long history. The (most probably) nineteenth-century author, Apdul Mutalip, advocated a more balanced view by pointing out some fundamental contributions the Chinese had made to the welfare of the Javanese; he also demonstrates that their presence in Java has a basis in law. Although seems like a poem in Javanese metre, his Sajarah Cina, written in Javanese, is remarkable not only for its subject matter but also for the way the material is presented, in a rhetoric unknown to exist in Javanese literature by most scholars.